2006
DOI: 10.1186/1471-2407-6-61
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid co-treatment induces resistance to chemotherapy in surgical resections, xenografts and established cell lines of pancreatic cancer

Abstract: These data show that DEX induces therapy resistance in pancreatic carcinoma cells and raise the question whether GC-mediated protection of tumour cells from cancer therapy may be dangerous for patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 32 publications
(33 reference statements)
2
27
1
Order By: Relevance
“…The results of Wang et al 87 however, can not be explained on the basis of cell kinetics. Thus, the results from our 6,90,91,95 and other studies in murine and human tumor xenografts indicate that, in GC-sensitive tumors, concurrent treatment with steroids and anticancer drugs may be contraindicated and that the effectiveness of cycle stage-specific agents may be considerably reduced due to unfavorable cell cycle distributions. On the other hand, GCs may add significantly to the effectiveness of a sequential chemotherapy program when used appropriately by altering the temporal relationship of the recovery events in the tumor and the normal tissues.…”
Section: © 2 0 0 8 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 70%
“…The results of Wang et al 87 however, can not be explained on the basis of cell kinetics. Thus, the results from our 6,90,91,95 and other studies in murine and human tumor xenografts indicate that, in GC-sensitive tumors, concurrent treatment with steroids and anticancer drugs may be contraindicated and that the effectiveness of cycle stage-specific agents may be considerably reduced due to unfavorable cell cycle distributions. On the other hand, GCs may add significantly to the effectiveness of a sequential chemotherapy program when used appropriately by altering the temporal relationship of the recovery events in the tumor and the normal tissues.…”
Section: © 2 0 0 8 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 70%
“…Prolonged elevation of glucocorticoids could have a direct impact upon tumorigenesis. It has been reported that glucocorticoids promote survival and proliferation of tumor cells and the chemotherapeutic resistance of tumor cells (13). However, the underlying mechanisms are largely unknown.…”
Section: Glucocorticoids Decrease P53 Protein Levels and Function In mentioning
confidence: 99%
“…Correspondingly, a huge amount of data suggests that GCs acutely induce resistance in normal and transformed cells of epithelial origin, including the majority of human solid malignant tumor cells. Tumors involved have been found to be derived from bladder, brain, breast, cervix, colon, liver, lung, kidney, ovary, pancreas, prostate, rectum and testis, and also neuroblastomas, melanomas and osteosarcomas are rendered therapy resistant by GCs [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. These GC-induced prosurvival effects may become clinically relevant when they interfere with the effect of chemotherapeutics [28].…”
mentioning
confidence: 99%